Exploring improvement plans of fourteen European integrated care sites for older people with complex needs - Stoop, Annerieke; de Bruin, Simone R.; Wistow, Gerald; Billings, Jenny; Ruppe, Georg; Leichsenring, Kai; Obermann, Konrad; Baan, Caroline A.; Nijpels, Giel (Health policy, 2019)
Integrated care programmes are increasingly being put in place to provide care to older people living at home. However, knowledge about further improving integrated care is limited. In fourteen integrated care sites in Europe, plans to improve existing ways of working were designed, implemented and evaluated to enlarge the understanding of what works and with what outcomes when improving integrated care. This paper provides insight into the existing ways that the sites were working with respect to integrated care, their perceived difficulties and their plans for working towards improvement. The seven components of the Expanded Chronic Care Model provided a conceptual framework for describing the fourteen sites. Although sites were spread across Europe and differed in basic characteristics and existing ways of working, a number of difficulties in delivering integrated care were similar. Existing ways of working and improvement plans mostly focused on three components of the Expanded Chronic Care Model: delivery system design; decision support; self-management. Two components were represented less frequently in existing ways of working and improvement plans: building healthy public policy; building community capacity. These findings suggest that broadly-based prevention efforts, population health promotion and community involvement remain limited. From the Expanded Chronic Care Model perspective, therefore, opportunities for improving integrated care outcomes may continue to be restricted by the narrow focus of developed improvement plans.